R-loops in normal and malignant hematopoiesis - Hirayama, Mayumi; Shinriki, Satoru; Matsui, Hirotaka (Frontiers in Hematology, 2023)
An R-loop is a nucleic acid structure consisting of a DNA:RNA hybrid and single-stranded DNA. It is formed physiologically in normal cells and is involved in transcription, replication, and gene rearrangement; in particular, it has multiple roles including in mitochondrial DNA replication and class switch recombination of immunoglobulin genes in B cells. However, accumulating evidence indicates aberrant R-loop formation in various malignancies, including hematopoietic neoplasms. The accumulation of such inappropriate R-loops can cause conflicts between transcription and DNA replication. This exacerbates genomic instability through the generation of DNA replication stress, that, in turn, leads to cellular phenotypic changes and disease progression. When RNAs are synthesized during transcription they hybridize with template DNA in cis, giving rise to R-loops. In addition, it was recently revealed that noncoding RNAs also form R-loops when bound to genomic DNA in trans. Together with such observations, new roles for the R-loop in disease development have been proposed. The relationship between inflammation and the R-loop has also attracted much attention. In this review, we will focus on the mechanisms of R-loop formation in various hematopoietic neoplasms and introduce the important findings from recent studies. Therapeutic concepts for targeting R-loop accumulation in hematopoietic neoplasms will also be discussed.